2010
DOI: 10.3892/or_00000993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stemness gene expression and CD133 abnormal methylation in neuroblastoma cell lines

Abstract: Abstract. Neuroblastoma is the most common extracranial solid tumor in children, accounting for up to 10% of all childhood malignancies. Cellular heterogeneity is a hallmark of this embryonal cancer, as distinct neural crest lineages can be found within the same tumor sample. The aim of our study was to investigate the presence of a subpopulation of immature cells with features of cancer-like stem cells in 10 neuroblastoma cell lines. RT-PCR and flow cytometry were performed in order to analyze different kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…CD133 and c-kit are considered to be markers of NB CSCs, CSC survival, growth regulation and poor clinical outcome[ 12 , 100 ]; GPRC5C is considered to indicate neuroectodermal origin and a differentiated embryonic stem cell state; Notch is involved in neural SC maintenance[ 101 - 103 ]; Pigf2 is involved in tumour angiogenesis growth and survival[ 104 ], and neurotrophin receptors are involved in NB growth, invasion and survival[ 16 , 100 ]. Other reverse transcription-polymerase chain reaction studies have reported increased CD133, Sox2, Bmi1 and Msi1 expression in immature NB CSC-like cells[ 105 ], and genome-wide microarray analysis of CSCs enriched from NB cell lines have identified Wnt, Notch, Shh and TGFβ signalling pathways in self-renewing CSC-like phenotypes, with TGFβ activation associated with repression of SMAD6 and SMAD7 TGFβ signalling repressors, Shh signalling associated with expression of Patched, Gli1 and smoothened, and CD133 and CD15 expression enriched in CSC-like neurospheres[ 106 ].…”
Section: Neuroblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…CD133 and c-kit are considered to be markers of NB CSCs, CSC survival, growth regulation and poor clinical outcome[ 12 , 100 ]; GPRC5C is considered to indicate neuroectodermal origin and a differentiated embryonic stem cell state; Notch is involved in neural SC maintenance[ 101 - 103 ]; Pigf2 is involved in tumour angiogenesis growth and survival[ 104 ], and neurotrophin receptors are involved in NB growth, invasion and survival[ 16 , 100 ]. Other reverse transcription-polymerase chain reaction studies have reported increased CD133, Sox2, Bmi1 and Msi1 expression in immature NB CSC-like cells[ 105 ], and genome-wide microarray analysis of CSCs enriched from NB cell lines have identified Wnt, Notch, Shh and TGFβ signalling pathways in self-renewing CSC-like phenotypes, with TGFβ activation associated with repression of SMAD6 and SMAD7 TGFβ signalling repressors, Shh signalling associated with expression of Patched, Gli1 and smoothened, and CD133 and CD15 expression enriched in CSC-like neurospheres[ 106 ].…”
Section: Neuroblastomamentioning
confidence: 99%
“…The mRNA-binding protein Musashi1 is a critical regulator of SC self-renewal and has been implicated in CSC-like self-renewal capacity in NB by promoting target mRNA translation and stem cell-fate transition[ 105 , 221 ]. Although the signalling mechanisms involved in Musashi1 function in stem/progenitor cells are unclear, Musashi1 is regulated by phosphorylation and by MAPK signalling in oocytes, and exhibits functional duality by promoting translation and repressing mRNA targets, in a similar way to Musashi2, which represses TGFβR1 mRNA, whilst activating translation of SMAD3 mRNA in proliferating K562 myelogenous leukemia cells[ 222 ].…”
Section: Molecules and Mechanisms That Promote Select And Maintain Nb Cscsmentioning
confidence: 99%
“…CD133, a penta-span, tri-membrane glycoprotein encoded by Prominin-1 was originally found to be expressed in human hematopoietic stem and progenitor cells. It is also reported to be highly expressed in several cancers, including GBM and NB, making the CD133 + CSC more metastatic and resistant to radiotherapy as well as chemotherapy [7,8,9]. CD133 + CSC possess the same functional properties such as the ability to differentiate and self-renew as their normal counterpart, thus contributing toward tumor initiation and proliferation.…”
Section: Introductionmentioning
confidence: 99%